The RAFT Telemedicine Network in Low and Middle Income Countries: Educational and Clinical Services, Lessons Learnt and Perspectives - Georges eBediang; Georges eBediang; Caroline ePerrin; Rafael Ruiz de eCastaneda; Yannick eKamga; Alexandre eSawadogo; Cheick Oumar Bagayoko; Antoine eGeissbuhler (Frontiers Media S.A., 2014)
Background: The objectives of this paper are to: i) provide an overview of the educational and clinical experiences of the RAFT network, ii) analyse key challenges and lessons learnt throughout a decade of activity and, iii) draw a vision and perspectives of its sustainability.Methods: The study was carried out following three main stages: i) a literature review, ii) the analysis of key documents and iii) discussions with key collaborators of the RAFT.Results: RAFT has been offering an important quantity of educational, clinical and public health activities during the last decade. The educational activities include: the weekly delivery of video-lectures for continuing and postgraduate medical education, the use of virtual patients for training in clinical decision making, research training activities using ICTs and other e-learning activities. The clinical and public health activities include: tele-expertise to support health professionals in the management of difficult clinical cases, the implementation of clinical information systems in African hospitals, the deployment of mHealth projects, etc. Since 2010, the RAFT has been extended to the Altiplano in Bolivia and Nepal (in progress). Lessons learnt and perspectives: Important lessons have been learnt from the accumulated experiences throughout these years. These lessons concern: social and organization, human resources, technologies and data security, policy and legislation, and economy and financing. Also, given the increase of the activities and the integration of eHealth and telemedicine in the health system of most of the countries, the RAFT network faces many other challenges and perspectives such as: learning throughout life, recognition and valorisation of teaching or learning activities, the impact evaluation of interventions, and the scaling up and transferability out of Africa of RAFT activities. Based on the RAFT experience, effective integration and optimum use of eHealth and telemedicine in LMICs